The Effectiveness of the Affiliate Marketing Model in Enhancing the Competitiveness of MSMEs in the Digital Economy Era - Andrianata, Mufid; suharsono, Judi; Wishal Nafis, Raihan; Fithrianto, M Novan (Jurnal Manajemen Dan Akuntansi Medan, 2025)
The digital transformation has compelled Micro, Small, and Medium Enterprises (MSMEs) to adopt adaptive marketing strategies that align with shifting consumer behaviors. One such emerging approach is affiliate marketing, which leverages incentive-based partnerships to expand online product visibility. This study was conducted to explore the effectiveness of affiliate marketing models in strengthening MSME competitiveness amid the growing challenges of the digital economy. This research employed a qualitative approach with an exploratory case study design. Data were collected through in-depth interviews with MSME actors, limited participatory observation, and documentation of digital marketing practices. The data were analyzed thematically to identify recurring patterns, strategic applications, and the impacts of affiliate marketing adoption. The findings reveal that MSMEs which strategically integrate affiliate models experience significant improvements in market reach, sales performance, and brand image. The most effective strategies involve selecting affiliates aligned with specific market segments, producing platform-appropriate promotional content, and conducting regular performance evaluations. Additionally, affiliates contribute to market education and provide valuable feedback that supports ongoing marketing development. In conclusion, affiliate marketing models prove to be effective instruments for driving MSME digital transformation and sustaining competitive advantage. Future research is recommended to explore the long-term sustainability of affiliate partnerships, the role of AI-based analytics in optimizing affiliate selection, and comparative studies across sectors and regions within the Indonesian MSME landscape.